Types of the Yakut Female Decorations Based on P. A. Oyunsky Articles - Efimova, Liudmila Stepanovna; Afanasev, Nyurgun Vyacheslavovich; Luginova, Oksana Afanasevna (Journal of History Culture and Art Research, 2018)
In the article, the authors consider the female decorations of the Yakut, based on the materials of Platon Alekseevich Oyunsky article “Yakut tale (olonkho): it’s plot and composition”. He is the first author to write about the Yakuts’ decorations based on the olonkho materials yet in 1927. P. A. Oyunsky is a famous writer, linguist, folklorist, outstanding public and state figure of the Yakut people. Terminology of the Yakut decorations is poorly studied in the Yakut linguistics. There are no monographic studies, aimed at analyzing the vocabulary of decorations in the Yakut language. That’s why P. A. Oyunsky article, containing interesting data on the Yakuts’ decorations, is one of the source materials in studying this issue. As the result, the authors come to conclusion that, P. A. Oyunsky was the first to analyze four types of the Yakuts female decorations in chapter “Female decorations” in his article. He left a full description of a big solid decoration, composed of a few elements. By implementing contrastive-comparative, lexico-semantic and descriptive methods, this research reveals female decorations in olonkho.